Film laminate and packaging material or container

By using aliphatic polyamide resins such as MXD6 and polyamide 6 in the film laminate, combining olefin-based elastomer, antioxidant and ionomer resin, an excellent film laminate structure is formed, and the film laminate in the prior art is solved The problem of insufficient thermal durability achieves mechanical properties and gas barrier properties after high temperature treatment.

CN119116509APending Publication Date: 2024-12-13UBE CORPORATION +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411020154.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-08-09
Filing Date
2016-10-25
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing membrane laminates lack thermal durability during the heating and sterilization process of food, making it difficult to maintain gas barrier properties and mechanical properties.

Method used

Using a film laminate composed of aliphatic polyamide resins such as MXD6 and polyamide 6, the olefin-based elastomer, antioxidant and ionomer resin are added to form excellent stretch forming properties through specific resin composition and layer structure design. and gas barrier.

Benefits of technology

It realizes excellent mechanical properties, bending fatigue resistance and transparency after hot water treatment and cooking treatment, and improves the thermal durability and gas barrier properties of the film laminate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119116509A_ABST
    Figure CN119116509A_ABST
Patent Text Reader

Abstract

Provided is a film laminate which has excellent stretch moldability, can maintain flexural fatigue resistance and breaking strength even after hot water treatment or retort treatment, and also has transparency and oxygen barrier properties. The film laminate is obtained by laminating a polyamide layer (A) containing a xylylene-based polyamide resin (a) as a main component, and a layer (B) comprising a polyamide resin composition, the polyamide resin composition contains 74-94 mass% of a polyamide resin (b), 0.1-2.8 mass% of an olefin elastomer, 0.01-3 mass% of an ionomer resin, and 5.5-20 mass% of a polyamide resin (c), the polyamide resin (b) being an aliphatic polyamide resin, and the polyamide resin (c) being a xylylene polyamide resin.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present application is a divisional application of an application with application number “201680063133.0”, application date October 25, 2016, and invention name “Film laminate and packaging material or container”. Technical Field

[0002] The present invention relates to a film laminate and a packaging material or a container using the film laminate. Background Art

[0003] Films formed from polyamide resin compositions (hereinafter, "films formed from polyamide resin compositions" may be referred to as "polyamide films") are excellent in various properties such as gas barrier properties, toughness, pinhole resistance, heat resistance, and transparency. Therefore, polyamide films are widely used in various fields.

[0004] Among them, polyamides obtained by the polycondensation reaction of xylylenediamine and aliphatic dicarboxylic acids, such as polyamides obtained by meta-xylylenediamine and adipic acid (hereinafter also referred to as "MXD6"), have high strength and high elastic modulus, and show low permeability to gaseous substances such as oxygen, carbon dioxide, odor and fragrance, and are therefore widely used as gas barrier materials in the field of packaging materials. Compared with other gas barrier resins, MXD6 has good thermal stability when melted, so it can be co-extruded and co-injected with thermoplastic resins such as polyethylene terephthalate (hereinafter abbreviated as "PET"), polyamide resin and polypropylene. Therefore, MXD6 is used as a gas barrier layer constituting a multilayer structure. In Patent Document 1, it is disclosed that a polyamide-based laminated film formed by laminating MXD6 and polyamide 6 is excellent in gas barrier properties, bending fatigue resistance, and transparency.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2001-341253 Summary of the invention

[0008] Problems to be solved by the invention

[0009] In addition, for example, when the film laminate is used as a food packaging member, the film laminate may be heated when the food is heat-sterilized. Therefore, in such a case, the film laminate is required to have excellent heat durability.

[0010] The main purpose of the present invention is to provide a film laminate having a layer with a specified xylene diamine-based polyamide resin such as MXD6 as the main component and a layer with an aliphatic polyamide resin such as polyamide 6 as the main component. The film laminate has excellent stretch formability and can maintain bending fatigue resistance and breaking strength even after hot water treatment and boiling treatment, and at the same time has better transparency and oxygen barrier properties.

[0011] Means used to solve problems

[0012] <1> A film laminate, which is a film laminate formed by laminating a polyamide layer (A) and a layer (B) formed of a polyamide resin composition, wherein the polyamide layer (A) contains a polyamide resin (a) as a main component, and the polyamide resin (a) has: a diamine unit containing 70 mol% or more of a diamine unit represented by the following general formula (I), and a dicarboxylic acid unit containing 50 mol% or more of a linear aliphatic dicarboxylic acid unit represented by the following general formula (II);

[0013] The polyamide resin composition comprises: 74 to 94% by mass of a polyamide resin (b), 0.1 to 2.8% by mass of an olefin-based elastomer, 0.01 to 3% by mass of an ionomer resin, and 5.5 to 20% by mass of a polyamide resin (c); the polyamide resin (b) is selected from a homopolymer of an aliphatic polyamide and a copolymer formed using two or more raw material monomers for forming the aliphatic polyamide resin homopolymer; the polyamide resin (c) is a polyamide resin having a diamine unit containing 70 mol % or more of a diamine unit represented by the general formula (I) and a dicarboxylic acid unit containing 50 mol % or more of a linear aliphatic dicarboxylic acid unit represented by the general formula (II).

[0014]

[0015] [In the general formula (II), m represents an integer of 2 to 18.]

[0016] <2> according to <1> The film laminate, wherein the polyamide resin composition further contains 0.01 to 1 mass % of an antioxidant.

[0017] <3> according to <1> or <2> The film laminate, wherein the polyamide resin (b) comprises polyamide 6.

[0018] <4> according to <1> ~ <3> The film laminate according to any one of the preceding claims, wherein the diamine unit of the polyamide resin (a) is derived from meta-xylylenediamine, para-xylylenediamine, or a mixture thereof.

[0019] <5> according to <1> ~ <4> The film laminate according to any one of the preceding claims, wherein the linear aliphatic dicarboxylic acid unit of the polyamide resin (a) is derived from adipic acid, sebacic acid or a mixture thereof.

[0020] <6> according to <1> ~ <5> The film laminate according to any one of the preceding claims, wherein the olefin-based elastomer comprises at least one of an ethylene-acrylic acid ester copolymer and an ethylene-methacrylic acid ester copolymer.

[0021] <7> according to <1> ~ <5> The film laminate according to any one of the preceding claims, wherein the olefin-based elastomer comprises an ethylene-ethyl acrylate copolymer, and a content of acrylic acid ester in the ethylene-ethyl acrylate copolymer is 5 to 30% by mass.

[0022] <8> according to <2> ~ <7> The film laminate according to any one of the preceding claims, wherein the antioxidant comprises a phenolic antioxidant.

[0023] <9> according to <1> ~ <8> The film laminate according to any one of the preceding claims, wherein the ionomer resin comprises at least one of an ethylene-methacrylic acid copolymer and an ethylene-acrylic acid copolymer.

[0024] <10> according to <1> ~ <9> The film laminate according to any one of the preceding claims, wherein the polyamide resin (c) is poly(meta-xylylene adipamide).

[0025] <11> according to <1> ~ <10> The film laminate according to any one of the above aspects is a stretched film laminate composed of a stretched film.

[0026] <12> according to <11> The film laminate, wherein the stretched film laminate is composed of a biaxially stretched film.

[0027] <13> according to <1> ~ <12> The film laminate according to any one of the above aspects, wherein a mass ratio of the ionomer resin to the olefin-based elastomer, that is, ionomer resin / olefin-based elastomer, is 0.04 to 0.4.

[0028] <14> according to <1> ~ <13> The film laminate according to any one of the preceding claims, wherein the olefin-based elastomer and the ionomer resin each independently contain at least one of an ethylene-methacrylic acid copolymer and an ethylene-acrylic acid copolymer.

[0029] <15> A packaging material having <1> ~ <14> The film laminate according to any one of the above.

[0030] <16> A container having <1> ~ <14> The film laminate according to any one of the above.

[0031] Effects of the Invention

[0032] According to the present invention, there can be provided a film laminate having excellent stretch formability, excellent gas barrier properties and transparency, and excellent mechanical properties and bending fatigue resistance even after retorting or hot water treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a schematic cross-sectional view of a film laminate according to one embodiment of the present invention. DETAILED DESCRIPTION

[0034] Although the description of the components of the present invention described below may be based on typical embodiments of the present invention, the present invention is not limited to such embodiments.

[0035] In this specification, the numerical range expressed by "to" means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit. In addition, "(meth)acrylic group" means both or either "acrylic group" and "methacrylic group".

[0036] The film laminate of the present invention is a film laminate having at least one polyamide layer (A) containing a polyamide resin (a) as a main component and a layer (B) formed of a polyamide resin composition, wherein the polyamide resin composition contains a polyamide resin (b), an olefin elastomer, an ionomer resin and a polyamide resin (c). The polyamide resin composition preferably contains an antioxidant.

[0037] In the film laminate of the present invention, in particular, the layer (B) containing the polyamide resin (b) is specified as a specific resin composition, and the components are specified as specific compounding amounts, thereby being able to produce the following film laminate: the obtained film laminate has excellent stretch formability during molding, and has excellent transparency and gas barrier properties, and has excellent bending fatigue resistance, breaking strength and interlayer adhesion strength even after boiling treatment and hot water treatment.

[0038] The layer structure of the film laminate of the present invention is not particularly limited as long as it has more than one layer (A) and layer (B), but from the viewpoint of improving the bending fatigue resistance of the film laminate, a two-layer structure such as layer (A) / layer (B), a three-layer structure such as layer (B) / layer (A) / layer (B), layer (A) / layer (B) / layer (A), a five-layer structure such as layer (B) / layer (A) / layer (B) / layer (A) / layer (B), layer (A) / layer (B) / layer (A) / layer (B), etc. is preferred. Among them, a three-layer structure of layer (B) / layer (A) / layer (B) can more effectively exert gas barrier properties, bending fatigue resistance, etc., so it is preferred. The number of layers constituting the film laminate of the present invention is preferably 2 to 10 layers, more preferably 2 to 6 layers, further preferably 2 to 4 layers, and particularly preferably 3 layers.

[0039] Figure 1 Schematic cross-sectional view of a preferred film stack according to this embodiment. Figure 1 As shown, the film laminate 1 of this embodiment is a three-layer structure of layer (B) / layer (A) / layer (B), and has a core layer 10 composed of layer (A) and skin layers 11 and 12 composed of layer (B). The skin layer 11 covers one surface 10a of the core layer 10. The skin layer 12 covers the other surface 10b of the core layer 10. In this way, the core layer 10 is sandwiched by the skin layers 11 and 12.

[0040] The film laminate of the present invention may contain other layers in addition to layer (A) and layer (B) according to the desired performance. Other layers may be arranged between layer (A) and layer (B) or on the outside of the skin layer. As other layers, adhesive layers (sealing layers, barrier layers, vapor-deposited layers) and the like may be cited. In the present invention, there are no other layers between layer (A) and layer (B). That is, preferably layer (B) is located on the surface of layer (A).

[0041] When the film laminate of the present invention has two or more layers (A), the respective layers (A) may have the same composition or different compositions.

[0042] When the film laminate of the present invention has two or more layers (B), the respective layers (B) may have the same composition or different compositions.

[0043] The thickness of the layer (A) is preferably 1 to 20 μm, more preferably 3 to 10 μm. When the laminate of the present invention has two or more layers (A), the thickness of each layer may be the same or different.

[0044] The thickness of the layer (B) is preferably 1 to 20 μm, more preferably 3 to 10 μm. When the laminate of the present invention has two or more layers (B), the thickness of each layer may be the same or different.

[0045] [Polyamide layer (A)]

[0046] In the film laminate of the present invention, layer (A) contains polyamide resin (a) as a main component. Here, the so-called "containing polyamide resin (a) as a main component" means that the mass ratio of polyamide resin (a) relative to the total mass of the components constituting layer (A) is 80% by mass or more, preferably 90% by mass, and more preferably 95% by mass or more. Layer (A) may contain only one polyamide resin (a) or may contain two or more. When containing two or more, the total amount is preferably in the above range.

[0047] In the film laminate of the present invention, layer (A) contains a polyamide resin (a) as a main component, and the polyamide resin (a) has a diamine unit containing 70 mol% or more of a diamine unit represented by the following general formula (I), and a dicarboxylic acid unit containing 50 mol% or more of a linear aliphatic dicarboxylic acid unit represented by the following general formula (II).

[0048]

[0049] [In the above general formula (II), m represents an integer of 2 to 18]

[0050] In the polyamide resin (a), the total amount of the diamine unit and the dicarboxylic acid unit is specified to be not more than 100 mol%. In addition, the polyamide resin (a) may further contain constituent units other than those described above within a range not impairing the effects of the present invention.

[0051] The diamine units in the polyamide resin (a) contain 70 mol% or more of the diamine units represented by the general formula (I) in the diamine units, preferably 80 mol% or more, more preferably 90 mol% or more, further preferably 95 mol% or more, and further preferably 98 mol% or more. The upper limit is preferably 100 mol%.

[0052] Examples of the compound that can constitute the diamine unit represented by the general formula (I) include o-xylylenediamine, m-xylylenediamine, and p-xylylenediamine. It is preferred that at least one of m-xylylenediamine and p-xylylenediamine is contained, and it is more preferred that m-xylylenediamine is contained. The compound that can constitute the diamine unit represented by the general formula (I) may be used alone or in combination of two or more.

[0053] Examples of the compound that can constitute the diamine unit represented by general formula (I) in the present invention include compounds containing 30 to 100 mol % of meta-xylylenediamine and 70 to 0 mol % of para-xylylenediamine, and preferably compounds containing 70 to 100 mol % of meta-xylylenediamine and 30 to 0 mol % of para-xylylenediamine.

[0054] Examples of compounds that can constitute the diamine unit other than the diamine unit represented by the general formula (I) include alicyclic diamines such as 1,2-bis(aminomethyl)cyclohexane, 1,3-bis(aminomethyl)cyclohexane, and 1,4-bis(aminomethyl)cyclohexane, aromatic diamines such as p-phenylenediamine, aliphatic diamines such as ethylenediamine, N-methylethylenediamine, 1,3-propylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, undecamethylenediamine, dodecamethylenediamine, 2-methyl-1,5-pentanediamine, and 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane, and polyether diamines having an ether bond such as Jeffamine and Elastamine (both trade names) manufactured by Huntsman Co., Ltd., but are not limited thereto. These can be used alone or in combination of two or more.

[0055] Regarding the dicarboxylic acid units in the polyamide resin (a), from the viewpoint of reactivity during polycondensation, and crystallinity and moldability of the polyamide resin (a), the dicarboxylic acid units contain a total of 50 mol% or more of the straight-chain aliphatic dicarboxylic acid units represented by the above general formula (II), preferably 70 mol% or more, more preferably 80 mol% or more, further preferably 90 mol% or more, further preferably 95 mol% or more, and further preferably 98 mol% or more. The upper limit is preferably 100 mol%.

[0056] In the above general formula (II), m represents an integer of 2 to 18, preferably 3 to 16, more preferably 4 to 12, further preferably 4 to 8, further preferably 4 to 6, and further preferably 4.

[0057] Examples of the compound that can constitute the linear aliphatic dicarboxylic acid unit represented by general formula (II) include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,10-decanedicarboxylic acid, 1,11-undecanedicarboxylic acid, and 1,12-dodecanedicarboxylic acid, preferably adipic acid and sebacic acid, and more preferably adipic acid. These can be used alone or in combination of two or more.

[0058] The type of the linear aliphatic dicarboxylic acid unit represented by the general formula (II) is appropriately determined according to the application. With regard to the linear aliphatic dicarboxylic acid unit in the polyamide resin (a), from the viewpoint of imparting excellent gas barrier properties to the polyamide resin (a) and maintaining heat resistance of the packaging material and packaging container after heat sterilization, it is preferred that the linear aliphatic dicarboxylic acid unit contain at least one selected from the group consisting of adipic acid unit, sebacic acid unit and 1,12-dodecane dicarboxylic acid unit in an amount of 50 mol % or more, more preferably 70 mol % or more, further preferably 80 mol % or more, and particularly preferably 90 mol % or more.

[0059] The above-mentioned “group consisting of adipic acid units, sebacic acid units and 1,12-dodecanedicarboxylic acid units” is preferably “a group consisting of adipic acid units and sebacic acid units”, and more preferably “adipic acid units”.

[0060] Regarding the linear aliphatic dicarboxylic acid units in the polyamide resin (a), it is preferred that the linear aliphatic dicarboxylic acid units contain 50 mol% or more of adipic acid units from the viewpoint of the gas barrier properties of the polyamide resin (a) and appropriate thermal properties such as glass transition temperature and melting point. In addition, regarding the linear aliphatic dicarboxylic acid units in the polyamide resin (a), it is preferred that the linear aliphatic dicarboxylic acid units contain 50 mol% or more of sebacic acid units from the viewpoint of imparting appropriate gas barrier properties and molding processability to the polyamide resin (a). When used for applications requiring low water absorption, weather resistance, and heat resistance, it is preferred that the linear aliphatic dicarboxylic acid units contain 50 mol% or more of 1,12-dodecane dicarboxylic acid units.

[0061] Examples of compounds that can constitute dicarboxylic acid units other than the dicarboxylic acid units represented by the above general formula (II) in the polyamide resin (a) include aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, and 2,6-naphthalenedicarboxylic acid; aliphatic dicarboxylic acids having a carbon number of 3 or less such as oxalic acid and malonic acid; and dicarboxylic acids having an unsaturated bond such as fumaric acid, maleic acid, 1,3-phenylenedicarboxylic acid, and 1,4-phenylenedicarboxylic acid, but are not limited thereto.

[0062] Regarding the polyamide resin (a), in order to give the polyamide resin (a) further gas barrier properties and to facilitate the molding processability of packaging materials and packaging containers, it is preferred that the dicarboxylic acid units contain a total of 0.1 mol% or more of aromatic dicarboxylic acid units, more preferably 0.5 to 15 mol%, and further preferably 1 to 10 mol%. As compounds that can constitute aromatic dicarboxylic acid units, terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, etc. can be exemplified, but are not limited to these. They can be used alone or in combination of two or more.

[0063] The type of aromatic dicarboxylic acid unit is appropriately determined according to the application, but it is preferred that the dicarboxylic acid unit contains an isophthalic acid unit and / or a terephthalic acid unit. The content ratio of the isophthalic acid unit and the terephthalic acid unit (isophthalic acid unit: terephthalic acid unit) is not particularly limited and can be appropriately determined according to the application. For example, from the viewpoint of a moderate glass transition temperature and reduced crystallinity, when the total of the two units is set to 100, the molar ratio of the isophthalic acid unit and the terephthalic acid unit (isophthalic acid unit: terephthalic acid unit) is preferably 0:100 to 100:0, more preferably 0:100 to 60:40, further preferably 0:100 to 40:60, and further preferably 0:100 to 30:70.

[0064] The number average molecular weight (Mn) of the polyamide resin (a) is not particularly limited, but is preferably 15,000 or more, more preferably 20,000 or more, and further preferably 23,000 or more. The number average molecular weight (Mn) of the polyamide resin (a) is preferably 35,000 or less, more preferably 30,000 or less, and further preferably 28,000 or less. When the number average molecular weight of the polyamide resin (a) is within the above range, a film laminate having good formability, excellent tensile mechanical properties and excellent impact strength can be obtained, and the unreacted products of the polyamide are few and the properties are stable. The number average molecular weight of the polyamide resin (a) can be obtained by the quantitative values ​​of the terminal amino group concentration and the terminal carboxyl group concentration by the following formula.

[0065] Number average molecular weight = 2 × 1,000,000 / ([NH2]+[COOH])

[0066] [NH2]: Terminal amino concentration (μeq / g)

[0067] [COOH]: Terminal carboxyl concentration (μeq / g)

[0068] In layer (A), in the range of not damaging the purpose and effect of the present invention, in addition to polyamide resin (a), various additives commonly used in polyamide resin can also be matched. As additives, for example, inorganic fillers, flame retardants, conductivity imparting agents, crystal nucleating agents, ultraviolet absorbers, antioxidants, vibration suppressants, antibacterial agents, insect repellents, deodorants, coloring inhibitors, heat stabilizers, mold release agents, antistatic agents, plasticizers, lubricants, colorants, pigments, dyes, foaming agents, foaming agents, anti-adhesion agents, stabilizers and coupling agents can be listed, but are not limited to these. These additives can each contain only one kind, or more than two kinds. Among them, the amount of these additives is preferably less than 10% by mass relative to the total mass of the components constituting layer (A), more preferably less than 5% by mass, more preferably less than 3% by mass, and more preferably less than 1% by mass. In the case of matching the above-mentioned additives, as the lower limit of the amount of matching, it is preferably more than 0.01% by mass relative to the total mass of the components constituting layer (A).

[0069] Furthermore, the layer (A) may contain a polyamide resin other than the polyamide resin (a) or other thermoplastic resin within a range not impairing the object and effects of the present invention.

[0070] The polyamide resin (a) can be produced by polycondensing a diamine component that can constitute the above-mentioned diamine unit and a dicarboxylic acid component that can constitute the above-mentioned dicarboxylic acid unit. The degree of polymerization can be controlled by adjusting the polycondensation conditions. During the polycondensation, a small amount of monoamine or monocarboxylic acid can be added as a molecular weight regulator. In addition, in order to suppress the polycondensation reaction and achieve the desired degree of polymerization, the ratio (molar ratio) of the diamine component and the dicarboxylic acid component constituting the polyamide resin (a) can be adjusted to deviate from 1.

[0071] As the polycondensation method of polyamide resin (a), reaction extrusion method, pressurized salt method, normal pressure dropping method, pressurized dropping method etc. can be listed, but are not limited to them. In addition, the reaction temperature is as low as possible, and the yellowing and gelation of polyamide resin (a) can be suppressed, and the polyamide resin (a) of stable properties can be obtained.

[0072] The reaction extrusion method is a method of melt-kneading a polyamide resin containing a diamine component and a dicarboxylic acid component in an extruder and reacting the polyamide resin. The raw materials used in the reaction extrusion method can be directly added to the diamine component and the dicarboxylic acid component, or can be added after being modulated into a polyamide salt or a polyamide oligomer having a number average molecular weight of less than 2000 using a polymerization kettle in advance. In addition, in order to prevent the deterioration of the polyamide resin, it is preferred to react under a nitrogen atmosphere while removing water with several sections of open vents or vacuum vents.

[0073] The pressurized salt method is a method of melt polycondensing nylon salt as a raw material under pressure. Specifically, after preparing a nylon salt aqueous solution containing a diamine component and a dicarboxylic acid component, the aqueous solution is concentrated, and then the temperature is raised under pressure to remove the condensation water while polycondensing. While slowly returning the tank to normal pressure, the temperature is raised to about the melting point of the polyamide resin (a) + 10°C and maintained, and then the pressure is further slowly reduced to 0.02MPaG, and the temperature is maintained at this state to continue polycondensation. If a certain stirring torque is reached, the tank is pressurized to about 0.3MPaG with nitrogen to recover the polyamide resin (a).

[0074] The atmospheric pressure dropping method is a method in which the dicarboxylic acid component is heated and melted under atmospheric pressure, and the diamine component is continuously dropped to cause polycondensation while removing the condensation water. At this time, the polycondensation reaction is carried out while the reaction system is heated in such a way that the reaction temperature is not lower than the melting point of the generated polyamide resin. Compared with the above-mentioned pressurized salt method, the atmospheric pressure dropping method has a large output per batch because water for dissolving salt is not used, and because the gasification and condensation of the raw material components are not required, the reaction rate is less reduced, which can shorten the process time.

[0075] The pressure drop method is a method in which a dicarboxylic acid component is first added to a polycondensation tank and heated to melt, and then the inside of the tank is pressurized to preferably about 0.3-0.4 MPaG, while the diamine component is continuously dropped to remove the condensation water and polycondensation is carried out. At this time, the reaction system is heated up in such a way that the reaction temperature is not lower than the melting point of the generated polyamide resin, and the polycondensation reaction is carried out. If the set molar ratio is reached, the dropwise addition of the diamine component is terminated, and the inside of the tank is slowly returned to normal pressure, while the temperature is raised to about the melting point of the polyamide resin (a) + 10°C and maintained, and then the pressure is further slowly reduced to 0.02 MPaG, and the temperature is maintained at this state to continue the polycondensation. If a certain stirring torque is reached, the inside of the tank is pressurized to about 0.3 MPaG with nitrogen, and the polyamide resin (a) is recovered.

[0076] Regarding the method for adjusting the melt viscosity, i.e., the number average molecular weight, of the polyamide resin (a), in addition to the method of determining the polymerization end point by the stirring torque in the above-mentioned polymerization method, there is also a method of adjusting the molar ratio to deviate from 1 in advance during the monomer feeding stage to thereby set the target number average molecular weight.

[0077] In the polycondensation of the polyamide resin (a), it is preferred to add a phosphorus atom-containing compound from the viewpoint of promoting the amidation reaction.

[0078] Examples of the phosphorus atom-containing compound include phosphinic acid compounds such as dimethylphosphinic acid and benzylphosphinic acid; phosphinic acid compounds such as hypophosphorous acid, sodium hypophosphite, potassium hypophosphite, lithium hypophosphite, magnesium hypophosphite, calcium hypophosphite, and ethyl hypophosphite; phosphonic acid compounds such as phosphonic acid, sodium phosphonate, potassium phosphate, lithium phosphate, potassium phosphate, magnesium phosphate, calcium phosphate, phenylphosphonic acid, ethylphosphonic acid, sodium phenylphosphonate, potassium phenylphosphonate, lithium phenylphosphonate, diethyl phenylphosphonate, sodium ethylphosphonate, and potassium ethylphosphonate; phosphinous acid compounds such as phosphinous acid, sodium phosphite, lithium phosphite, potassium phosphite, magnesium phosphite, calcium phosphite, phenylphosphinous acid, sodium phenylphosphite, potassium phosphite, lithium phenylphosphite, and ethyl phenylphosphite; and phosphorous acid compounds such as phosphorous acid, sodium hydrogen phosphite, sodium phosphite, lithium phosphite, potassium phosphite, magnesium phosphite, calcium phosphite, triethyl phosphite, triphenyl phosphite, and pyrophosphorous acid.

[0079] Among them, especially hypophosphite metal salts such as sodium hypophosphite, potassium hypophosphite, lithium hypophosphite have a high effect of promoting the amidation reaction and are also excellent in coloration prevention effect, so they are preferably used, and sodium hypophosphite is particularly preferred. In addition, the phosphorus atom-containing compound that can be used in the present invention is not limited to these compounds.

[0080] The amount of the phosphorus atom-containing compound added is preferably 0.1 to 1000 mass ppm, more preferably 1 to 600 mass ppm, and further preferably 5 to 400 mass ppm, based on the phosphorus atom concentration of the polyamide resin (a). If the amount of the phosphorus atom-containing compound added is 0.1 mass ppm or more, the polyamide resin (a) is difficult to color during polycondensation, and the transparency becomes high. If the amount of the phosphorus atom-containing compound added is 1000 mass ppm or less, the polyamide resin (a) is difficult to gel, and it is also possible to reduce the fish eye (fish eye) that is believed to be caused by the phosphorus atom-containing compound and mixed into the molded product, and the appearance of the molded product becomes good.

[0081] In addition, in the polycondensation system of the polyamide resin (a), it is preferred to add an alkali metal compound together with a phosphorus atom-containing compound. In order to prevent the coloration of the polyamide resin (a) during polycondensation, a sufficient amount of the phosphorus atom-containing compound needs to be present in the polycondensation system of the polyamide resin (a), but this may cause gelation of the polyamide resin (a) as the case may be, so in order to adjust the amidation reaction rate, it is also preferred to allow the alkali metal compound to coexist.

[0082] As the alkali metal compound, alkali metal hydroxide, alkali metal acetate, alkali metal carbonate, alkali metal alkoxide, etc. are preferred. As specific examples of the alkali metal compound that can be used in the present invention, lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, lithium acetate, sodium acetate, potassium acetate, rubidium acetate, cesium acetate, sodium methoxide, sodium ethoxide, sodium propoxide, sodium butoxide, potassium methoxide, lithium methoxide, sodium carbonate, etc. can be cited, but it is not limited to these compounds and can be used. In addition, from the viewpoint of polymerization rate control and the viewpoint of reducing yellowness, the molar ratio of the phosphorus atom-containing compound to the alkali metal compound is preferably in the range of phosphorus atom-containing compound: alkali metal compound = 1.0:0.05 to 1.0:1.5, more preferably 1.0:0.1 to 1.0:1.2, and further preferably 1.0:0.2 to 1.0:1.1.

[0083] [Layer (B) formed of polyamide resin composition]

[0084] In the film laminate of the present invention, layer (B) is composed of a polyamide resin composition.

[0085] [Polyamide resin composition]

[0086] As described above, the film laminate of the present invention includes the layer (B) composed of the polyamide resin composition.

[0087] In addition, the polyamide resin composition contains: 74 to 94% by mass of polyamide resin (b), 0.1% to 2.8% by mass of olefin elastomer, 0.01% to 3% by mass of ionomer resin, and 5.5% to 20% by mass of polyamide resin (c). Here, the polyamide resin (b) is selected from a homopolymer of aliphatic polyamide and a copolymer formed by using two or more raw monomers to form the homopolymer of the aliphatic polyamide resin, and the polyamide resin (c) is a polyamide resin having a diamine unit containing 70% or more of the diamine unit represented by the general formula (I) and a dicarboxylic acid unit containing 50% or more of the straight-chain aliphatic dicarboxylic acid unit represented by the general formula (II). In the present invention, the polyamide resin composition preferably further contains 0.01% to 1% by mass of an antioxidant. In addition, in the polyamide resin composition of the present invention, the total of the polyamide resin (b), the olefin elastomer, the antioxidant, the ionomer resin and the polyamide resin (c) is set to 100% by mass.

[0088] In the film laminate of the present invention, by setting the layer (B) containing the polyamide resin (b) to a specific composition and setting the various components to a specific compounding amount, the obtained film laminate has excellent stretch formability during molding, and the obtained film laminate has excellent transparency and gas barrier properties, and also has excellent bending fatigue resistance, breaking strength retention rate and interlayer adhesion after boiling treatment and hot water treatment.

[0089] In the past, in a film laminate having a layer with MXD6 as the main component and a layer with polyamide 6 as the main component, an olefin-based elastomer as a soft component was added to polyamide 6 to improve flexibility, but there was a problem that the transparency of the film laminate was reduced due to the addition of the soft component. In contrast, in the present invention, an olefin-based elastomer is added to the layer (B) containing a specified polyamide resin (b) such as polyamide 6 to form a polyamide resin composition with a specific amount of a specific additive, so that a film laminate having transparency that is a compromise between flexibility and flexibility can be obtained. Furthermore, the film laminate of the present invention can adjust the crystallinity and stretchability of the layer (B) containing polyamide 6 as the main component by making the polyamide resin composition containing polyamide 6 as the main component into a specific composition, and as a result, the molding processability of the film laminate with the layer (A) containing polyamide resin (a) as the main component is improved.

[0090] [Polyamide resin (b)]

[0091] In the film laminate of the present invention, the polyamide resin composition constituting the layer (B) contains the polyamide resin (b).

[0092] Examples of the polyamide resin (b) include homopolymers of aliphatic polyamides and copolymers formed using a plurality of raw material monomers thereof (i.e., aliphatic polyamide resins, and homopolymers or copolymers). Specific examples of homopolymers of aliphatic polyamides and copolymers formed using a plurality of raw material monomers thereof include polycaprolactam (polyamide 6), polyundecanamide (polyamide 11), polydodecaneamide (polyamide 12), polyethylene adipamide (polyamide 26), polytetramethylene succinamide (polyamide 44), polytetramethylene glutaramide (polyamide 45), polytetramethylene adipamide (polyamide 46), polytetramethylene suberamide (polyamide 48), polytetramethylene azelaic acid amide (polyamide 49), polytetramethylene sebacic acid amide (polyamide 41), polytetramethylene succinamide (polyamide 42), polytetramethylene glutaramide (polyamide 43), polytetramethylene adipamide (polyamide 44), polytetramethylene succinamide (polyamide 45), polytetramethylene adipamide (polyamide 46), polytetramethylene suberamide (polyamide 48), polytetramethylene azelaic acid amide (polyamide 49), polytetramethylene sebacic acid amide (polyamide 41 0), polytetramethylene dodecanamide (polyamide 412), polypentamethylene succinamide (polyamide 54), polypentamethylene glutaramide (polyamide 55), polypentamethylene adipamide (polyamide 56), polypentamethylene suberamide (polyamide 58), polypentamethylene azelaic acid amide (polyamide 59), polypentamethylene sebacamide (polyamide 510), polypentamethylene dodecanamide (polyamide 512), polyhexamethylene succinamide (polyamide 64), polyhexamethylene glutaramide (polyamide 65), polyhexamethylene adipamide (polyamide 66), polyhexamethylene Suberamide (polyamide 68), polyhexamethylene azelaic acid amide (polyamide 69), polyhexamethylene sebacic acid amide (polyamide 610), polyhexamethylene dodecanamide (polyamide 612), polyhexamethylene tetradecamide (polyamide 614), polyhexamethylene hexadecanoic acid amide (polyamide 616), polyhexamethylene octadecanoic acid amide (polyamide 618), polynonamethylene adipamide (polyamide 96), polynonamethylene suberamide (polyamide 98), polynonamethylene azelaic acid amide (polyamide 99), polynonamethylene sebacic acid amide (polyamide 910), polynonamethylene dodecanamide ( Polyamide 912), polydecamethylene adipamide (polyamide 106), polydecamethylene suberamide (polyamide 108), polydecamethylene azelaic acid amide (polyamide 109), polydecamethylene sebacic acid amide (polyamide 1010), polydecamethylene dodecanamide (polyamide 1012), polydodecamethylene adipamide (polyamide 126), polydodecamethylene suberamide (polyamide 128), polydodecamethylene azelaic acid amide (polyamide 129), polydodecamethylene sebacic acid amide (polyamide 1210), polydodecamethylene dodecanamide (polyamide 1212), etc.

[0093] Among the specific examples of the above-mentioned polyamide resins, it is more preferred to use at least one homopolymer selected from the group consisting of polycaprolactam (polyamide 6), polyundecaneamide (polyamide 11), polydodecaneamide (polyamide 12), polyhexamethylene adipamide (polyamide 66), polyhexamethylene sebacamide (polyamide 610), polyhexamethylene dodecanamide (polyamides 6 and 12), polydecamethylene sebacamide (polyamide 1010), polydecamethylene dodecanamide (polyamide 1012) and polydodecaneamide (polyamide 1212), and / or a copolymer formed using a plurality of raw material monomers forming the same. It is further preferred to use at least one homopolymer selected from the group consisting of polycaprolactam (polyamide 6), polyundecaneamide (polyamide 11), polydodecaneamide (polyamide 12) and polyhexamethylene adipamide (polyamide 66), and / or a copolymer formed using a plurality of raw material monomers forming the same. Polycaprolactam (polyamide 6) is particularly preferred.

[0094] The content of the polyamide resin (b) in the polyamide resin composition is 74% by mass or more, preferably 80% by mass or more, and more preferably 85% by mass or more, from the viewpoint of flexibility and bending fatigue resistance. In addition, from the viewpoint of the formability, interlayer delamination and barrier properties of the film laminate, the content of the polyamide resin (b) in the polyamide resin composition is preferably 94% by mass or less, and more preferably 90% by mass or less.

[0095] The polyamide resin (b) may be used alone or in combination of two or more. When two or more polyamide resins are used, the total amount is preferably within the above range.

[0096] [Polyamide resin (c)]

[0097] In the film laminate of the present invention, the polyamide resin composition constituting layer (B) includes polyamide resin (c). The film laminate of the present invention can improve the interlayer adhesion between layer (A) and layer (B) by containing polyamide resin (c) in the polyamide resin composition constituting layer (B). As polyamide resin (c), the same resin as the polyamide resin (a) constituting polyamide layer (A) can be exemplified. That is, polyamide resin (c) is preferably a polyamide resin having a diamine unit containing 70 mol% or more of the diamine unit represented by the general formula (I) and a dicarboxylic acid unit containing 50 mol% or more of the straight-chain aliphatic dicarboxylic acid unit represented by the general formula (II).

[0098] In addition, examples of other polyamide resins (c) include polyisoxylyl adipamide (polyamide MXD6), polyisoxylyl suberamide (polyamide MXD8), polyisoxylyl azelaic acid amide (polyamide MXD9), polyisoxylyl sebacic acid amide (polyamide MXD10), polyisoxylyl dodecanamide (polyamide MXD12), polyisoxylyl terephthalamide (polyamide MXDT), polyisoxylyl isophthalamide (polyamide MXDI), polyisoxylyl hexahydroterephthalamide (polyamide MXDT(H)), Polyisophthalamide (polyamide MXDN), polyisophthalamide (polyamide PXD6), polyisophthalamide (polyamide PXD8), polyisophthalamide (polyamide PXD9), polyisophthalamide (polyamide PXD10), polyisophthalamide (polyamide PXD12), polyisophthalamide (polyamide PXDT), polyisophthalamide (polyamide PXDI), polyisophthalamide (polyamide PXDT(H)), polyisophthalamide (polyamide PXD10), polyisophthalamide (polyamide PXD12), polyisophthalamide (polyamide PXD2), polyisophthalamide (polyamide PXD3), polyisophthalamide (polyamide PXD4), polyisophthalamide (polyamide PXD5), ​​polyisophthalamide (polyamide PXD6), polyisophthalamide (polyamide PXD7), polyisophthalamide (polyamide PXD8), polyisophthalamide (polyamide PXD9), polyisophthalamide (polyamide PXD10 ... phenylenediamine naphthalamide (polyamide PXDN), polyparaphenylene terephthalamide (PPTA), polyparaphenylene isophthalamide (PPIA), polymetaphenylene terephthalamide (PMTA), polymetaphenylene isophthalamide (PMIA), poly(2,6-naphthalenediamine adipamide) (polyamide 2,6-BA polyamide 6), poly(2,6-naphthalenediamine suberamide) (polyamide 2,6-BAN8), poly(2,6-naphthalenediamine azelaic acid amide) (polyamide 2,6-BAN9), poly(2,6-naphthalenediamine decamethamide) (polyamide 2,6-BAN9), poly(2,6-naphthalenediamine decamethamide) Polyamides having an aromatic ring as a diamine component, such as polyamide 2,6-BAN10, poly(2,6-naphthalenedimethylene dodecanamide) (polyamide 2,6-BAN12), poly(2,6-naphthalenedimethylene terephthalamide) (polyamide 2,6-BANT), poly(2,6-naphthalenedimethylene isophthalamide) (polyamide 2,6-BANI), poly(2,6-naphthalenedimethylene hexahydroterephthalamide) (polyamide 2,6-BANT(H)), and poly(2,6-naphthalenedimethylene naphthalamide) (polyamide 2,6-BANN).

[0099] Examples of the polyamide resin (c) include polytetramethylene terephthalamide (polyamide 4T), polytetramethylene isophthalamide (polyamide 4I), polytetramethylene hexahydroterephthalamide (polyamide 4T (H)), polytetramethylene naphthalamide (polyamide 4N), polypentamethylene terephthalamide (polyamide 5T), polypentamethylene isophthalamide (polyamide 5I), polypentamethylene hexahydroterephthalamide (polyamide 5T (H)), polypentamethylene naphthalamide (polyamide 5N), polyhexamethylene terephthalamide (polyamide 6T), polyhexamethylene isophthalamide (polyamide 6I), polyhexamethylene hexahydroterephthalamide (polyamide 6T (H)), polypentamethylene naphthalamide (polyamide 6N), polyhexamethylene terephthalamide (polyamide 6T), polyhexamethylene isophthalamide (polyamide 6I), polyhexamethylene hexahydroterephthalamide (polyamide 6T (H)), polytetramethylene naphthalamide (polyamide 6N), polypentamethylene terephthalamide (polyamide 6T), polyhexamethylene isophthalamide (polyamide 6I), polyhexamethylene hexahydroterephthalamide (polyamide 6T (H)), polypentamethylene naphthalamide (polyamide 6N), polypentamethylene terephthalamide (polyamide 6T), polypent ... amide 6T (H)), polyhexamethylene naphthalamide (polyamide 6N), poly (2-methylpentamethylene terephthalamide) (polyamide M5T), poly (2-methylpentamethylene isophthalamide) (polyamide M5I), poly (2-methylpentamethylene hexahydroterephthalamide) (polyamide M5T (H)), poly (2-methylpentamethylene naphthalamide) (polyamide M5N), poly nonamethylene terephthalamide (polyamide 9T), poly nonamethylene isophthalamide (polyamide 9I), poly nonamethylene hexahydroterephthalamide (polyamide 9T (H)), poly nonamethylene naphthalamide (polyamide 9N), poly (2-methyl octamethylene terephthalamide) ( polyamide M8T), poly(2-methyloctamethylene isophthalamide) (polyamide M8I), poly(2-methyloctamethylene hexahydroterephthalamide) (polyamide M8T(H)), poly(2-methyloctamethylene naphthalamide) (polyamide M8N), polytrimethylhexamethylene terephthalamide (polyamide TMHT), polytrimethylhexamethylene isophthalamide (polyamide TMHI), polytrimethylhexamethylene hexahydroterephthalamide (polyamide TMHT(H)), polytrimethylhexamethylene naphthalamide (polyamide TMHN), polydecamethylene terephthalamide (polyamide 10T), polydecamethylene isophthalamide (polyamide 10I), polydecamethylene Polyamides having an aromatic ring as a dicarboxylic acid component, such as hexahydromethylene terephthalamide (polyamide 10T (H)), decamethylene naphthalamide (polyamide 10N), polyundecamethylene terephthalamide (polyamide 11T), polyundecamethylene isophthalamide (polyamide 11I), polyundecamethylene hexahydroterephthalamide (polyamide 11T (H)), polyundecamethylene naphthalamide (polyamide 11N), polydodecamethylene terephthalamide (polyamide 12T), polydodecamethylene isophthalamide (polyamide 12I), polydodecamethylene hexahydroterephthalamide (polyamide 12T (H)), and polydodecamethylene naphthalamide (polyamide 12N).

[0100] Further, examples of the polyamide resin (c) include poly(1,3-cyclohexanedimethylene adipamide) (polyamide 1,3-BAC6), poly(1,3-cyclohexanedimethylene suberamide) (polyamide 1,3-BAC8), poly(1,3-cyclohexanedimethylene azelaic acid amide) (polyamide 1,3-BAC9), poly(1,3-cyclohexanedimethylene sebacic acid amide) (polyamide 1,3-BAC10), poly(1,3-cyclohexanedimethylene dodecanamide) (polyamide 1,3-BAC12), poly(1,3-cyclohexanedimethylene terephthalamide) (polyamide 1,3-BACT), poly(1,3-cyclohexanedimethylene isophthalamide) (polyamide 1,3-BAC9). ACI), poly(1,3-cyclohexanedimethylene hexahydroterephthalamide) (polyamide 1,3-BACT(H)), poly(1,3-cyclohexanedimethylenenaphthalamide) (polyamide 1,3-BACN), poly(1,4-cyclohexanedimethyleneadipamide) (polyamide 1,4-BAC6), poly(1,4-cyclohexanedimethyleneoctanedimide) (polyamide 1,4-BAC8), poly(1,4-cyclohexanedimethylenenonazelamide) (polyamide 1,4-BAC9), poly(1,4-cyclohexanedimethylenedecahydroterephthalamide) (polyamide 1,4-BAC10), poly(1,4-cyclohexanedimethylenedodecanoamide) (polyamide 1,4-BAC12), poly(1,4-cyclohexanedimethylenehexahydroterephthalamide) (polyamide 1,4-BAC13), poly(1,4-cyclohexanedimethylenehexahydroterephthalamide) (polyamide 1,4-BAC14), poly(1,4-cyclohexanedimethylenehexahydroterephthalamide) (polyamide 1,4-BAC15), poly(1,4-cyclohexanedimethylenehexahydroterephthalamide) (polyamide 1,4-BAC16), poly(1,4-cyclohexanedimethylenehexahydroterephthalamide) (polyamide 1,4-BAC17), poly(1,4-cyclohexanedimethylenehexahydroterephthalamide) (polyamide 1,4-BAC18), poly(1,4-cyclohexanedimethylenehexahydroterephthalamide) (polyamide 1,4-BAC19), poly(1,4-cyclohexanedimethylenehexahydroterephthalamide) (polyamide 1,4-BAC1 1,4-BACT), poly(1,4-cyclohexanedimethyleneisophthalamide)(polyamide 1,4-BACI), poly(1,4-cyclohexanedimethylenehexahydroterephthalamide)(polyamide 1,4-BACT(H)), poly(1,4-cyclohexanedimethylenenaphthalamide)(polyamide 1,4-BACN), poly(4,4'-methylenebiscyclohexylene adipamide)(polyamide PACM6), poly(4,4'-methylenebiscyclohexyleneoctanamide)(polyamide PACM8), poly(4,4'-methylenebiscyclohexylenenonamide)(polyamide PACM9), poly(4,4'-methylenebiscyclohexylenesebaconamide)(polyamide Polyamide PACM10), poly(4,4'-methylenebicyclohexylene dodecanamide) (polyamide PACM12), poly(4,4'-methylenebicyclohexylene tetradecanoamide) (polyamide PACM14), poly(4,4'-methylenebicyclohexylene hexadecanoamide) (polyamide PACM16), poly(4,4'-methylenebicyclohexylene octadecanoamide) (polyamide PACM18), poly(4,4'-methylenebicyclohexylene terephthalamide) (polyamide PACMT), poly(4,4'-methylenebicyclohexylene isophthalamide) (polyamide PACMI), poly(4,4'-methylenebicyclohexylene hexahydroterephthalamide) (polyamide PACMT(H) ...4'-methylenebis(cyclohexylene naphthalene diamide)(polyamide PACMN), poly(4,4'-methylenebis(2-methyl-cyclohexylene) adipamide)(polyamide MACM6), poly(4,4'-methylenebis(2-methyl-cyclohexylene) suberamide)(polyamide MACM8), poly(4,4'-methylenebis(2-methyl-cyclohexylene) azelaic acid amide)(polyamide MACM9), poly(4,4'-methylenebis(2-methyl-cyclohexylene) sebacic acid amide)(polyamide MACM10), poly(4,4'-methylenebis(2-methyl-cyclohexylene) dodecanamide)(polyamide MACM 12), poly (4,4'-methylenebis (2-methyl-cyclohexylene) tetradecamide) (polyamide MACM14), poly (4,4'-methylenebis (2-methyl-cyclohexylene) hexadecamide) (polyamide MACM16), poly (4,4'-methylenebis (2-methyl-cyclohexylene) octadecamide) (polyamide MACM18), poly (4,4'-methylenebis (2-methyl-cyclohexylene) terephthalamide) (polyamide MACMT), poly (4,4'-methylenebis (2-methyl-cyclohexylene) isophthalamide) (polyamide MACMI), poly (4,4'-methylenebis (2-methyl-cyclohexylene) methyl-cyclohexylene)hexahydroterephthalamide)(polyamide MACMT(H)), poly(4,4'-methylenebis(2-methyl-cyclohexylene)naphthalene diamide)(polyamide MACMN), poly(4,4'-propylene bicyclohexylene adipamide)(polyamide PACP6), poly(4,4'-propylene bicyclohexylene octanamide)(polyamide PACP8), poly(4,4'-propylene bicyclohexylene azelaic acid amide)(polyamide PACP9), poly(4,4'-propylene bicyclohexylene sebacic acid amide)(polyamide PACP10), poly(4,4'-propylene bicyclohexylene dodecanamide)( Polyamide PACP12), poly(4,4'-propylene bicyclohexylene tetradecanoamide) (polyamide PACP14), poly(4,4'-propylene bicyclohexylene hexadecanoamide) (polyamide PACP16), poly(4,4'-propylene bicyclohexylene octadecanoamide) (polyamide PACP18), poly(4,4'-propylene bicyclohexylene terephthalamide) (polyamide PACPT), poly(4,4'-propylene bicyclohexylene isophthalamide) (polyamide PACPI), poly(4,4'-propylene bicyclohexylene hexahydroterephthalamide) (polyamide PACPT(H) ...(H)), poly(4,4'-propylene bicyclohexylene hexahydroterephthalamide) (polyamide PACPT(H)), poly(4,4'-propylene bicyclohexylene isophthalamide) (polyamide PACPI(H)), poly(4,4'-propylene bicyclohexylene hexahydroterephthalamide) (polyamide PACPT(H)), poly(4,4'-propylene bicyclohexylenePolyamides having alicyclic diamines and alicyclic dicarboxylic acids such as polyamides (polyamides) such as polyisophorone adipamide (polyamide IPD6), polyisophorone suberamide (polyamide IPD8), polyisophorone azelaic acid amide (polyamide IPD9), polyisophorone sebacic acid amide (polyamide IPD10), polyisophorone dodecanamide (polyamide IPD12), polyisophorone terephthalamide (polyamide IPDT), polyisophorone isophthalamide (polyamide IPDI), polyisophorone hexahydroterephthalamide (polyamide IPDT (H)), and polyisophorone naphthalene diamide (polyamide IPDN). As the polyamide resin (c), these polyamide resins may be used as raw material monomers, or copolymers using a plurality of them may be used.

[0101] As the polyamide resin (c), one of the above-mentioned polyamide resins may be used alone, or a plurality of polyamide resins may be used as a mixture.

[0102] Among the specific examples of the polyamide resin (c), polyisoxylylene adipamide (polyamide MXD6) and polyisoxylylene sebacamide (polyamide MXD10) are more preferably used, and polyisoxylylene adipamide is further preferably used. In addition, in the film laminate of the present invention, from the viewpoint of improving the interlayer adhesion between the polyamide layer (A) and the layer (B) formed by the polyamide resin composition, the polyamide resin (c) in the polyamide resin composition and the polyamide resin (a) constituting the polyamide layer (A) are preferably independently polyamide resins having diamine units represented by the general formula (I) containing 70 mol % or more, and dicarboxylic acid units containing 50 mol % or more of the linear aliphatic dicarboxylic acid units represented by the following general formula (II), and are more preferably the same polyamide resins.

[0103] From the viewpoint of improving the adhesion to the layer (A) formed by the polyamide resin (a), the content of the polyamide resin (c) in the polyamide resin composition is preferably 5.5% by mass or more, more preferably 7% by mass or more. In addition, from the viewpoint of suppressing the reduction of flexibility and tensile processability, the content of the polyamide resin (c) in the polyamide resin composition is preferably 20% by mass or less, more preferably 18% by mass or less, and further preferably 15% by mass or less.

[0104] The mass ratio of the polyamide resin (b) to the polyamide resin (c) (polyamide resin (b) / polyamide resin (c)) in the polyamide resin composition is preferably 6-15, more preferably 8-10, and even more preferably 8.5-9.

[0105] [Olefin elastomer]

[0106] In the film laminate of the present invention, the polyamide resin composition constituting the layer (B) contains an olefin-based elastomer.

[0107] The olefin-based elastomer in the present invention is a polymer obtained by copolymerizing at least one selected from ethylene and propylene and at least one selected from α,β-unsaturated carboxylic acid monomers and unsaturated carboxylic acid ester monomers.

[0108] Examples of the α,β-unsaturated carboxylic acid monomer include acrylic acid and methacrylic acid.

[0109] Examples of the α,β-unsaturated carboxylic acid ester monomers include methyl ester, ethyl ester, propyl ester, butyl ester, pentyl ester, hexyl ester, heptyl ester, octyl ester, nonyl ester, decyl ester of these unsaturated carboxylic acids, and mixtures thereof.

[0110] As olefin-based elastomers, there can be listed ethylene·α,β-unsaturated carboxylic acid copolymers, propylene·α,β-unsaturated carboxylic acid copolymers, ethylene·propylene·α,β-unsaturated carboxylic acid copolymers, ethylene·α,β-unsaturated carboxylic acid ester copolymers, propylene·α,β-unsaturated carboxylic acid ester copolymers, ethylene·propylene·α,β-unsaturated carboxylic acid ester copolymers, ethylene·α,β-unsaturated carboxylic acid / unsaturated carboxylic acid ester copolymers, propylene·α,β-unsaturated carboxylic acid / unsaturated carboxylic acid ester copolymers, and ethylene·propylene·α,β-unsaturated carboxylic acid / unsaturated carboxylic acid ester copolymers.

[0111] As the olefin-based elastomer, the above-mentioned olefin-based elastomers may be used alone or in combination of a plurality of types.

[0112] Among them, ethylene-(meth)acrylate copolymers obtained by copolymerizing ethylene and (meth)acrylate monomers are preferred, and specifically, ethylene-ethyl acrylate copolymers, ethylene-methyl acrylate copolymers, ethylene-ethyl methacrylate copolymers, etc. Among them, ethylene-ethyl acrylate copolymers are preferably used as olefin-based elastomers from the viewpoints of thermal stability during molding and effects of addition in small amounts.

[0113] The olefin-based elastomer used in the present invention is particularly preferably an ethylene-(meth)acrylate copolymer having a mass ratio of an olefin component such as ethylene to a (meth)acrylate component (olefin component such as ethylene:(meth)acrylate component) in the range of 90:5 to 70:30.

[0114] In the present invention, it is particularly preferred that the content of the (meth)acrylate in the ethylene-(meth)acrylate copolymer is 5 to 30% by mass. By setting the content within such a range, the pinhole resistance of the multilayer film can be further improved.

[0115] In the polyamide resin composition of the present invention, the content of the olefinic elastomer is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, further preferably 0.7% by mass or more, and particularly preferably 1% by mass or more, from the viewpoint of the bending fatigue resistance of the obtained film laminate. In addition, from the viewpoint of maintaining the transparency of the film laminate, the content of the olefinic elastomer in the polyamide resin composition is preferably 2.8% by mass or less, more preferably 2.5% by mass or less, particularly preferably 2.0% by mass or less, and further preferably 1.5% by mass or less.

[0116] [Antioxidant]

[0117] The polyamide resin composition constituting the layer (B) of the film laminate of the present invention preferably contains an antioxidant. As the antioxidant, phenolic antioxidants represented by IRGANOX1098, hindered amine antioxidants, phosphorus antioxidants represented by IRGAFOS168, sulfur antioxidants, hydrazine antioxidants, amide antioxidants, etc. can be cited, but phenolic antioxidants are preferably used in the present invention. In the polyamide resin composition of the present invention, by using a phenolic antioxidant, thickening during molding and the like are less likely to occur, and the mechanical properties such as breaking strength after steaming treatment are better maintained. Specific examples of phenolic antioxidants include bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate][ethylenebis(oxyethylene)] (trade name: IRGANOX245), N',N'-bis-3-(3'-5'-di-tert-butyl-4'-hydroxyphenyl) propionyl hexanediamine (trade name: IRGANOX1098), pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] (trade name: IRGANOX1010), etc. Among them, N',N'-bis-3-(3'-5'-di-tert-butyl-4'-hydroxyphenyl) propionyl hexanediamine (trade name: IRGANOX1098) is preferably used.

[0118] As the antioxidant, the above antioxidants may be used alone or in combination of a plurality of antioxidants.

[0119] In the polyamide resin composition, the content of the antioxidant is preferably 0.01% by mass to 1% by mass. By setting the content of the antioxidant to 0.01% by mass or more, the reduction in mechanical properties and the reduction in bending resistance after the hot water treatment of the film laminate can be suppressed. From the same viewpoint, the content of the antioxidant is more preferably 0.05% by mass or more, more preferably 0.08% by mass or more, and more preferably 0.1% by mass or more. In addition, the upper limit of the content of the antioxidant is preferably 1% by mass or less, more preferably 0.8% by mass or less, more preferably 0.5% by mass or less, and more preferably 0.3% by mass or less from the viewpoint of material cost with practicality.

[0120] [Ionomer resin]

[0121] The polyamide resin composition constituting the layer (B) of the film laminate of the present invention contains an ionomer resin.

[0122] The ionomer resin is an olefin / unsaturated carboxylic acid copolymer obtained by partially neutralizing (crosslinking by metal ions) the side chain carboxyl groups of the main chain composed of olefin units and unsaturated carboxylic acid units with metal ions.

[0123] Examples of the olefin include ethylene and propylene, and ethylene is preferably used. As the α,β-unsaturated carboxylic acid, acrylic acid and methacrylic acid are preferably used, but other unsaturated carboxylic acid ester monomers may also be copolymerized.

[0124] In the present invention, the ionomer resin preferably contains at least one of an ethylene-methacrylic acid copolymer and an ethylene-acrylic acid copolymer.

[0125] As metal ion components for neutralizing carboxyl groups, alkali metal ions such as lithium ion, sodium ion, potassium ion, magnesium ion, calcium ion, strontium ion, barium ion, alkaline earth metal ions, and aluminum ion, tin ion, titanium ion, manganese ion, iron ion, nickel ion, copper ion, zinc ion, cadmium ion, etc. can be listed. Only one of these metal ion components can be used, or two or more can be used. Among these, zinc ion and sodium ion are preferably used as metal ion components from the viewpoint of improving affinity with polyamide resin, and zinc ion is more preferred. The neutralization degree of the carboxyl group of the ionomer resin (the ratio of the number of neutralized carboxyl groups to the total number of carboxyl groups (the ratio of the number of neutralized carboxyl groups / the total number of carboxyl groups) × 100 (unit: %)) is preferably 20% to 80%, and more preferably 30% to 70%. When the neutralization degree of the carboxyl group of the ionomer resin is 20% or more, the transparency of the layer (B) constituting the film laminate is better, so it is preferred. When the degree of neutralization of the carboxyl group of the ionomer resin is 80% or less, a decrease in the melt fluidity of the ionomer resin can be avoided, and the transparency of the film laminate 1 is further improved, which is preferred.

[0126] From the viewpoint of improving the compatibility of each component of the polyamide resin composition and improving transparency, the content of the ionomer resin in the polyamide resin composition is preferably 0.01 mass % or more in the polyamide resin composition, more preferably 0.05 mass % or more, and further preferably 0.1 mass % or more. Similarly, from the viewpoint of the transparency of the film laminate, it is preferably 3 mass % or less, more preferably 0.5 mass % or less. The ionomer resin can contain only one kind in the polyamide resin composition, or it can contain more than two kinds. When containing more than two kinds, the total amount is preferably the above range.

[0127] In addition, the ionomer resin may react with each other or other components in the film laminate, but it is needless to say that such a case is also included in the scope of the film laminate of the present invention.

[0128] In the present invention, the mass ratio of the ionomer resin to the olefin elastomer in the polyamide resin composition (ionomer resin / olefin elastomer) is preferably 0.04 to 0.4. The lower limit of the mass ratio is more preferably 0.05 or more, and the upper limit of the mass ratio is more preferably 0.3 or less. By setting it to such a range, the tensile elastic modulus of the film laminate tends to be further improved.

[0129] In particular, when the olefin-based elastomer and the ionomer resin each independently contain at least one of an ethylene-methacrylic acid copolymer and an ethylene-acrylic acid copolymer, the compatibility of the two is improved, and the above-mentioned effects can be more effectively exerted.

[0130] [Other ingredients]

[0131] In the polyamide resin composition constituting layer (B), in the range of not damaging the purpose of the present invention and the effect of action, various additives commonly used in polyamide resins can also be matched. As additives, for example, inorganic fillers, flame retardants, conductivity imparting agents, crystal nucleating agents, ultraviolet absorbers, vibration suppressants, antibacterial agents, insect repellents, deodorants, coloring inhibitors, heat stabilizers, mold release agents, antistatic agents, plasticizers, lubricants, colorants, pigments, dyes, foaming agents, foaming agents, anti-adhesion agents, stabilizers and coupling agents can be listed, but are not limited to these. These additives can only include 1 kind, or more than 2 kinds. Wherein, the amount of these additives is preferably less than 10% by mass relative to the total mass of the components constituting layer (B), more preferably less than 5% by mass, more preferably less than 3% by mass, and more preferably less than 1% by mass. In the case of matching the above-mentioned additives, as the lower limit of the amount of matching, it is preferably more than 0.01% by mass relative to the total mass of the components constituting layer (B).

[0132] Furthermore, the layer (B) may contain a thermoplastic resin other than the polyamide resin within a range not impairing the object and effects of the present invention.

[0133] [Molding of film laminate]

[0134] The film laminate of the present invention can be produced by, for example, a known film laminate production method using the polyamide resin composition and the polyamide resin (a) (when layer (A) contains components other than the polyamide resin (a), a composition containing the polyamide resin (a)).

[0135] As a method for manufacturing a film laminate, for example, a casting method, a tubular method, etc. In the casting method, for example, raw materials such as polyamide resin (a) and polyamide resin composition constituting each layer are melted through multiple extruders, and co-extruded into a flat film using a T-die or a hanger-type die, cast on a casting roll surface, and then cooled to manufacture a film, thereby manufacturing an unstretched film laminate.

[0136] In the tubular method, for example, an unstretched film laminate can be produced by air cooling or water cooling a tubular product melt-extruded into a cylindrical shape using an annular die.

[0137] Alternatively, the polyamide resin (a) and the film formed of the polyamide resin composition may be extruded into films and then heat-pressed to form an unstretched film laminate. Alternatively, the films may be bonded together with an adhesive.

[0138] The film laminate obtained by manufacturing in this way can also be used in an unstretched state, but from the viewpoint of the strength and gas barrier properties of the obtained film laminate, it is preferably biaxially stretched and used as a biaxially stretched film laminate. In addition, whether the film laminate is stretched can be confirmed by (the determination of the refractive index, etc.) of the film laminate.

[0139] In addition, the unstretched film laminate is preferably preheated before stretching. The preheating temperature is preferably in the range of 75°C to 150°C, more preferably 80°C to 140°C. By setting the preheating temperature to this temperature range, a stretched film laminate with less uneven stretching and excellent mechanical properties can be obtained. In addition, the preheating time (the time from the start of preheating to stretching) is preferably in the range of 5 seconds to 60 seconds, more preferably 7 seconds to 40 seconds, and further preferably 10 seconds to 30 seconds. By setting the preheating time to this time, a stretched film laminate with less uneven stretching and excellent mechanical properties can be obtained.

[0140] Next, the stretching of the obtained unstretched film laminate can be carried out, for example, by a conventionally known industrial method. For example, as a method for biaxially stretching the unstretched film laminate obtained by the casting method, for example, a simultaneous biaxial stretching method, a successive biaxial stretching method, and a tubular stretching method can be cited. In the simultaneous biaxial stretching method, the unstretched sheet is stretched longitudinally and transversely simultaneously using a tenter-type simultaneous biaxial stretching machine. In the successive biaxial stretching method, the unstretched sheet melt-extruded by the T-die is stretched longitudinally with a roller stretching machine, and then stretched transversely with a tenter-type stretching machine. In the tubular stretching method, the tubular sheet formed by the annular die is stretched longitudinally and transversely into an inflation type under the pressure of the gas. The stretching process can be continuously implemented immediately after the manufacture of the film laminate, or the film laminate can be temporarily wound and then stretched as another process.

[0141] The stretching ratio of the film laminate varies with the intended use, but in the manufacturing process using a T-die, from the viewpoint of the stretchability of the polyamide resin itself, the longitudinal and transverse stretching ratios are preferably 1.5 times or more and 5.0 times or less, and more preferably 2.0 times or more and 4.0 times or less. If the stretching ratio of either the longitudinal or transverse direction of the film laminate is 5.0 times or less, the fracture frequency in the stretching process can be more effectively suppressed to a lower level.

[0142] The temperature of the cooling roller is preferably 20°C to 50°C, more preferably 30°C to 45°C. When the temperature of the cooling roller is lower than 50°C, the growth of crystals in the film laminate can be suppressed, so that the obtained film laminate has transparency. On the other hand, when the temperature of the cooling roller is higher than 20°C, the strength of the film laminate after stretching can be maintained.

[0143] The stretching temperature is preferably 30° C. to 250° C., more preferably 50° C. to 220° C. When the stretching temperature is 30° C. or higher, the breakage frequency in the stretching process can be suppressed. When the stretching temperature is 250° C. or lower, in addition to suppressing the breakage frequency in the stretching process, the film laminate after stretching can also be made excellent in strength and transparency.

[0144] It is preferred that the film laminate stretched by the above method is further subjected to heat treatment. By subjecting the stretched film to heat treatment, dimensional stability at room temperature can be imparted to the stretched film laminate. The heat treatment temperature of the stretched film laminate at this time is preferably above 100°C and below 250°C, more preferably above 150°C and below 220°C. When the heat treatment temperature of the stretched film laminate is above 100°C, the thermal process is sufficient, the shrinkage of the stretched film laminate after winding is suppressed, and the dimensional stability is excellent. When the heat treatment temperature of the stretched film laminate is below 250°C, the stretched film laminate has excellent transparency.

[0145] The stretched film laminate that has been sufficiently thermally fixed by the heat treatment operation can be cooled and rolled up according to a conventional method.

[0146] By setting the stretching ratio and processing conditions within the above ranges, the strength and gas barrier properties of the obtained film laminate can be ensured, and the film laminate can be stably handled without breaking during stretching.

[0147] Furthermore, in order to improve printability, lamination, and adhesive imparting properties, the film laminate may be subjected to surface treatments such as corona discharge treatment, plasma treatment, flame treatment, and acid treatment. In addition, after the film laminate is subjected to the above-mentioned surface treatment as required, it can be used for the respective purposes through secondary processing steps such as printing, lamination, adhesive coating, and heat sealing.

[0148] The film laminate of the present invention is preferably used as a packaging material or a container. Examples of the packaging material or container of the present invention include packaging materials for food, medical use, and cosmetics, and packaging materials for food are preferred.

[0149] Examples of the contents that can be filled or packaged in the packaging material or container of the present invention include rice snacks, bean snacks, nuts, biscuits, cookies, wafers, marshmallows, pies, half-baked cakes, candies, snack foods and the like; staple foods such as bread, snack noodles, instant noodles, dried noodles, pasta, aseptically packaged rice, porridge, porridge, packaged rice cakes, and string foods; agricultural processed products such as pickles, boiled beans, natto, miso, frozen tofu, tofu, nameko, konjac, wild vegetable processed products, jams, peanut butter, salads, frozen vegetables, and potato processed products; livestock processed products such as ham, bacon, sausages, chicken processed products, and corned beef; fish processed products such as ham, bacon, sausages, chicken processed products, and corned beef; Processed seafood products such as meat ham, fish sausage, seafood minced meat, fish cakes, seaweed, soy sauce boiled food, seasoned bonito, salted fish, smoked salmon, spicy cod roe, etc.; fruit meat such as peach, orange, pineapple, apple, pear, cherry, etc.; vegetables such as corn, asparagus, mushroom, onion, carrot, white radish, potato, etc.; cooked foods such as frozen dishes and refrigerated dishes represented by hamburgers, meatballs, fried seafood, dumplings, and croquettes; dairy products such as butter, margarine, cheese, cream, instant cream powder, and formula milk powder; food such as liquid seasoning, sterilized bag curry, pet food, etc.; cigarettes, disposable hand warmers, medicines, cosmetics, etc.

[0150] In addition, after the packaging material or container of the present invention is filled or packaged with the stored object, the packaging material or container can be sterilized in a form suitable for the stored object. Examples of the sterilization method include heat sterilization such as boiling treatment below 100°C, semi-boiling treatment above 100°C, boiling treatment, and high boiling treatment above 130°C, electromagnetic wave sterilization such as ultraviolet rays, microwaves, and gamma rays, gas treatment such as ethylene oxide, and chemical sterilization such as hydrogen peroxide and hypochlorous acid.

[0151] Example

[0152] Hereinafter, the present invention will be described in more detail based on specific examples, but the present invention is not limited to the following examples and can be implemented with appropriate changes within the scope of the gist.

[0153] In addition, the following materials were used in the following Examples and Comparative Examples.

[0154] Polyamide resin (a), polyamide resin (c): poly(m-xylylene adipamide) (MXD6), trade name: MXNYLON S6011 (manufactured by Mitsubishi Gas Chemical Co., Ltd.)

[0155] Polyamide resin (b): polyamide 6, hereinafter also referred to as "PA6", trade name: UBE NYLON 1022B (manufactured by Ube Industries, Ltd.)

[0156] Olefin elastomer: ethylene-ethyl acrylate copolymer, hereinafter also referred to as "EEA", trade name: UBEPOLYETHYLENE ZE708 (manufactured by Ube Maruzen Polyethylene Co., Ltd.), the content of acrylic acid ester in the ethylene-ethyl acrylate copolymer is 16% by mass.

[0157] Antioxidant: Phenolic antioxidant, IRGANOX 1098 (manufactured by BASF)

[0158] Ionomer resin: Ethylene-methacrylic acid copolymer Zn 2+ Ionomer, the neutralization degree of carboxyl groups of the ionomer resin is 60%, trade name: HIMILAN 1706 (manufactured by Mitsui & DuPont Co., Ltd.)

[0159] (Example 1)

[0160] Using a multilayer film extruder with two extruders, the layer (A) formed by the polyamide resin (a) and the layer (B) formed by the polyamide resin composition are formed in a three-layer structure of (B) layer / (A) layer / (B) layer. When the extrusion temperature of the layer (A) formed by the polyamide resin (a) is set to 260°C, the extrusion temperature of the layer (B) formed by the polyamide resin composition is set to 250°C, and the feed block and T-die temperature are set to 250°C, extrusion molding is performed. In addition, a pinning device is used during film laminate molding, and a voltage of 6.5KV is applied. In addition, the temperature of the cooling roller is set to 20°C. The thickness of each layer is set to 45μm / 45μm / 45μm, and an unstretched multilayer film (unstretched film laminate) with a total thickness of 135μm is obtained. Next, the unstretched multilayer film was stretched to 3×3 times by a simultaneous biaxial stretching machine (manufactured by Toyo Seiki Seisaku-sho, EX10-S5) to obtain a multilayer stretched film (stretched film laminate) having a total thickness of 15 μm. The stretching was performed at a preheating temperature of 80° C., a preheating time of 30 seconds, a heat setting temperature of 215° C., a heat setting time of 30 seconds, and a stretching speed of 3 m / min.

[0161] Regarding the polyamide resin composition, 88.7% by mass of polyamide 6 as a polyamide resin (b), 1% by mass of UBE POLYETHYLENE ZE708 (EEA) as an olefin-based elastomer, 0.1% by mass of IRGANOX 1098 as an antioxidant, 0.2% by mass of HIMILAN 1706 as an ionomer resin, and 10% by mass of MXD6 (MXD6NYLON S6011) as a polyamide resin (c) were mixed by a dry mixer and then put into an extruder for use.

[0162] (Example 2)

[0163] A film laminate was produced in the same manner as in Example 1 except that the preheating temperature during the stretching process was 140°C.

[0164] (Comparative Example 1)

[0165] A film laminate was produced in the same manner as in Example 1 except that the (B) layer was composed of polyamide 6 alone.

[0166] (Comparative Example 2)

[0167] A film laminate was produced in the same manner as in Example 2 except that the (B) layer was composed of polyamide 6 alone.

[0168] (Comparative Example 3)

[0169] Film formation was carried out in the same manner as in Example 2 except that a polyamide 6 single-layer film (thickness: 135 μm) was used.

[0170] (Example 3)

[0171] A film laminate was produced in the same manner as in Example 1 except that no antioxidant was added to the polyamide resin composition.

[0172] (Comparative Example 5)

[0173] A film laminate was produced in the same manner as in Example 1 except that the ionomer resin of the polyamide resin composition was not added.

[0174] (Comparative Example 6)

[0175] A film laminate was produced in the same manner as in Example 1 except that the amount of the olefin-based elastomer added to the polyamide resin composition was 3% by mass.

[0176] (Comparative Example 7)

[0177] A film laminate was produced in the same manner as in Example 1 except that the amount of the polyamide resin (c) added in the polyamide resin composition was 5% by mass and no ionomer resin was added.

[0178] (Comparative Example 8)

[0179] A film laminate was produced in the same manner as in Example 1 except that the amount of the polyamide resin (c) added in the polyamide resin composition was 25% by mass and no ionomer resin was added.

[0180] (Comparative Example 9)

[0181] A film laminate was produced in the same manner as in Example 1 except that the antioxidant of the polyamide resin composition, the ionomer resin and the polyamide resin (c) were not added.

[0182] (Comparative Example 10)

[0183] A film laminate was produced in the same manner as in Example 1 except that the olefin-based elastomer of the polyamide resin composition, the antioxidant, and the polyamide resin (c) were not added.

[0184] (productivity)

[0185] In Examples 1 to 3 and Comparative Examples 1 to 3 and Comparative Examples 5 to 10, the case where no breakage occurred after 10 stretching processes was performed was evaluated as "○", and the case where breakage occurred during stretching was evaluated as "×".

[0186] (Bending fatigue resistance of film laminate after hot water treatment)

[0187] The multilayer stretched films (film laminates) prepared in Examples 1 to 3 and Comparative Examples 1 to 3 and Comparative Examples 5 to 10 were subjected to hot water treatment at 135°C for 30 minutes. The film after hot water treatment was subjected to 1000 bending tests in accordance with MIL-B-131C at 23°C and 50% relative humidity (RH) using a Gelbo Flex Tester with a thermostatic bath manufactured by Rigaku Kogyo Co., Ltd., and then the film laminate was placed on a recording paper and smeared with ink to measure the number of black dots recorded on the recording paper. As a result, a number of less than 5 was judged as "○", and a number of more than 5 was judged as "×".

[0188] (Oxygen barrier properties)

[0189] The oxygen permeability of the multilayer stretched films (film laminates) prepared in Examples 1 to 3 and Comparative Examples 1 to 3 and Comparative Examples 5 to 10 was measured at 23°C and 60%RH using a gas permeation rate measuring device (MOCON-OX-TRAN 2 / 20 manufactured by Modern Control) in accordance with ASTM D-3985. The obtained results are shown in Table 1.

[0190] (Retention rate of breaking strength after retorting (%))

[0191] The tensile strength at break of the multilayer stretched film obtained in the Examples or Comparative Examples after humidity conditioning for one week at 23°C and 50% RH was measured using a tensile testing machine (manufactured by Toyo Seiki Seisaku-sho, Ltd., product name "Strograph V1-C" in accordance with ASTM D882, and the average value obtained by measuring 8 times was taken as the tensile strength at break before steaming treatment.

[0192] Next, the multilayer stretched film obtained in the example or comparative example was subjected to a retort treatment at 121°C for 30 minutes using an autoclave (SR-240) manufactured by TOMY SEIKO CO., LTD. After the retort treatment, the film was humidified at 23°C and 50% RH for 1 week, and the tensile strength at break was measured. The average value obtained by measuring 8 times was taken as the breaking strength after the retort treatment. The breaking strength after the retort treatment was divided by the breaking strength (longitudinal direction) value obtained before the treatment × 100 and taken as the breaking strength retention rate (unit: %).

[0193] Breaking strength retention rate (%) = ((breaking strength after retorting) / (breaking strength before retorting)) × 100

[0194] (Interlayer Adhesion of Film Laminate after Retorting)

[0195] The film laminate after the tensile breaking strength test of the multilayer stretched film subjected to the retorting treatment was visually observed to confirm whether there was interlayer delamination on the fracture surface of the film laminate. The result of the visual observation was judged as "○" if no interlayer delamination was observed, and "×" if a little interlayer delamination was observed.

[0196] (Haze)

[0197] The haze was measured using a haze value measuring device (manufactured by Nippon Denshoku Industries, product name "COH-400A") according to JIS-K-7105. The sample was a multilayer stretched film obtained in an example or comparative example before hot water treatment, and the haze was measured after humidity adjustment at 23°C and 50% RH for one week.

[0198]

[0199] As shown in these results, the film laminate (multilayer stretched film) obtained in this embodiment is excellent in molding processability by making the polyamide resin composition constituting the (B) layer a specific resin composition. In addition, the obtained multilayer stretched film has excellent gas barrier properties and transparency. Specifically, in Examples 1 and 2, even if the preheating temperature during stretching is a wide temperature range of 80°C to 140°C, the film laminate can be stretched, and the obtained stretched film laminate can obtain excellent properties such as transparency. Furthermore, even if the obtained multilayer stretched film is subjected to hot water treatment and boiling treatment, the bending fatigue resistance and breaking strength are almost not reduced, the mechanical properties are excellent, and no interlayer peeling between layer (A) and layer (B) occurs.

[0200] On the other hand, the multilayer stretched films of Comparative Examples 1 and 2, in which the (B) layer is composed only of polyamide 6, have low bending fatigue resistance after hot water treatment, and low fracture strength retention and interlayer adhesion after boiling treatment. In addition, when the polyamide resin composition constituting the (B) layer of the film laminate does not contain an antioxidant (Example 3), the fracture strength retention after boiling treatment is slightly poor, but still at a practical level. When the polyamide resin composition constituting the (B) layer does not contain an ionomer resin (Comparative Example 5) and when the content of the olefin-based elastomer is too high (Comparative Example 6), the haze of the film laminate deteriorates. When the polyamide resin composition constituting the (B) layer does not contain an ionomer resin and the content of the polyamide resin (c) is small (Comparative Example 7), the interlayer adhesion becomes weak, and when the content of the polyamide resin (c) is too high (Comparative Example 8), the molding processability is reduced, and the bending fatigue resistance after hot water treatment is reduced. When the polyamide resin composition constituting the (B) layer is composed of only two components, polyamide 6 and an olefin-based elastomer (Comparative Example 9), the haze is poor and the retention rate of breaking strength after retorting treatment is reduced. In addition, when the polyamide resin composition constituting the (B) layer is composed of only polyamide 6 and an ionomer resin (Comparative Example 10), the molding processability is reduced, and the bending fatigue resistance after hot water treatment, the retention rate of breaking strength after retorting treatment, and the interlayer adhesion are also reduced.

[0201] (Tensile elastic modulus)

[0202] The polyamide resin composition was prepared by blending polyamide 6 as polyamide resin (b), MXD6 (MXD6 NYLON S6011) as polyamide resin (c), UBE POLYETHYLENE ZE708 (EEA) as olefin elastomer, and HIMILAN 1706 as ionomer resin in the mass ratios shown in Table 2.

[0203] The obtained polyamide resin composition was molded into an unstretched monolayer film having a thickness of 100 μm according to Example 1. Furthermore, the unstretched monolayer film was stretched to obtain a stretched monolayer film having a thickness of 15 μm. The tensile elastic modulus of the obtained stretched monolayer film was measured in an atmosphere of 23° C. and 50% RH using a tensile tester (manufactured by A&D, TENSILON universal material testing machine RTA-10KN) in accordance with ASTM D-882. The results are shown in Table 2 below.

[0204] Table 2

[0205]

[0206] In the above Table 2, the MD direction (Machine Direction) refers to the conveying direction when the film is produced, and the TD direction (Transverse Direction) refers to the direction perpendicular to the MD direction.

[0207] As is clear from the above results, it was confirmed that the tensile modulus was significantly increased when the mass ratio of the olefin elastomer to the ionomer resin was in the range of Experimental Examples A to D. That is, it was found that the film laminate of the present invention can achieve a high tensile modulus when the mass ratio of the olefin elastomer to the ionomer resin is about 0.04 to 0.4.

[0208] Explanation of symbols

[0209] 1. Film laminate

[0210] 10 core layers

[0211] 11, 12 cortex

Claims

1. A film laminate, which is a film laminate formed by laminating a polyamide layer (A) and a layer (B) formed of a polyamide resin composition, wherein the polyamide layer (A) is composed only of a polyamide resin (a), and the polyamide resin (a) has: a diamine unit containing 70 mol% or more of a diamine unit represented by the following general formula (I), and a dicarboxylic acid unit containing 50 mol% or more of a linear aliphatic dicarboxylic acid unit represented by the following general formula (II); The polyamide resin composition comprises: 74 to 94% by mass of a polyamide resin (b), 0.1 to 2.8% by mass of an olefin-based elastomer, 0.01 to 3% by mass of an ionomer resin, and 5.5 to 20% by mass of a polyamide resin (c); The polyamide resin (b) is selected from a homopolymer of an aliphatic polyamide and a copolymer formed using two or more raw material monomers for forming the homopolymer of the aliphatic polyamide resin; The polyamide resin (c) is a polyamide resin having a diamine unit containing 70 mol % or more of the diamine unit represented by the general formula (I) and a dicarboxylic acid unit containing 50 mol % or more of the linear aliphatic dicarboxylic acid unit represented by the general formula (II); In the general formula (II), m represents an integer of 2-18.

2. The film laminate according to claim 1, wherein: The polyamide resin composition further contains 0.01 to 1 mass % of an antioxidant.

3. The film laminate according to claim 1 or 2, wherein: The polyamide resin (b) includes polyamide 6.

4. The film laminate according to any one of claims 1 to 3, wherein The diamine unit of the polyamide resin (a) is derived from meta-xylylenediamine, para-xylylenediamine or a mixture thereof.

5. The film laminate according to any one of claims 1 to 4, wherein The linear aliphatic dicarboxylic acid unit of the polyamide resin (a) is derived from adipic acid, sebacic acid or a mixture thereof.

6. The film laminate according to any one of claims 1 to 5, wherein The olefin-based elastomer includes at least one of an ethylene-acrylate copolymer and an ethylene-methacrylate copolymer.

7. The film laminate according to any one of claims 1 to 5, wherein The olefin-based elastomer includes an ethylene-ethyl acrylate copolymer, and the content of acrylic acid ester in the ethylene-ethyl acrylate copolymer is 5 to 30% by mass.

8. The film laminate according to any one of claims 2 to 7, wherein The antioxidant comprises a phenolic antioxidant.

9. The film laminate according to any one of claims 1 to 8, wherein The ionomer resin includes at least one of an ethylene-methacrylic acid copolymer and an ethylene-acrylic acid copolymer.

10. The film laminate according to any one of claims 1 to 9, wherein The polyamide resin (c) is poly(meta-xylylene adipamide). 11 . The film laminate according to claim 1 , which is a stretched film laminate composed of a stretched film.

12. The film laminate according to claim 11, wherein The stretched film laminate is composed of a biaxially stretched film.

13. The film laminate according to any one of claims 1 to 12, wherein The mass ratio of the ionomer resin to the olefin-based elastomer, ie, ionomer resin / olefin-based elastomer, is 0.04 to 0.

4.

14. The film laminate according to any one of claims 1 to 13, wherein The olefin-based elastomer and the ionomer resin each independently contain at least one of an ethylene-methacrylic acid copolymer and an ethylene-acrylic acid copolymer. 15 . A packaging material comprising the film laminate according to claim 1 . 16 . A container comprising the film laminate according to claim 1 .

Citation Information

Patent Citations

  • Biaxially stretched film for food packaging

    EP0620244A1

  • Heat-sealable laminated film having high dimensional stability

    JP1993064868A

  • Polyamide laminate film

    JP2001341253A

  • Polyamide laminated film

    JP2002187246A

  • Biaxially stretched laminated polyamide-based film

    JP2010234552A